Dados abertos governamentais : uma análise aplicada ao Ministério Público do Trabalho - Paulo, Joelson de Souza (2018)
In face of the development and stimulation of open government data - OGD in the various spheres of public authorities, whether in the Executive, Legislative, Judiciary or even the Public Prosecutor's Office, it is clear the challenge to public agencies regarding the need to manage this informational asset in a way strategy. The management of open government data has as its intrinsic basis the planning, control and development of positive actions for the strengthening of democracy and the exercise of citizenship, since it promotes public transparency and facilitates access to information for exercising social control. This master´s dissertation verifies the compliance of the open government data in the Ministério Público do Trabalho - MPT in face of trends and regulations at national and international level, providing them with subsidies for elaboration of a OGD model. In addition, it analyzes the Ministério Público da União - MPU, identifying the strategies and actions that guide the publication and dissemination of OGD. A qualitative methodological approach is adopted, through the accomplishment of bibliographical and documentary research developed to prospect theoretical concepts, understanding of the investigated problem and presentation of the main assumptions for a OGD management . The results have revealed that, despite the identification of available initiatives and OGD publication in MPT, they still occur in a limited way, lacking integration in a context of organizational strategy and well developed management so that they can provide aligned results to the principles and goals outlined